(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In this paper, we first introduce the class of partial symmetric spaces and then prove somefixed point theorems in such spaces.We introduce an analogue of the Hausdorff metric in the context ofpartial symmetric spaces and utilize the same to prove an analogue of the Nadler contraction principle insuch spaces. Our results extend and improve many results in the existing literature. We also give someexamples exhibiting the utility of our newly established results.